2012
DOI: 10.4067/s0716-97602012000300009
|View full text |Cite
|
Sign up to set email alerts
|

In Osteoporosis, differentiation of mesenchymal stem cells (MSCs) improves bone marrow adipogenesis

Abstract: The formation, maintenance, and repair of bone tissue involve close interlinks between two stem cell types housed in the bone marrow: the hematologic stem cell originating osteoclasts and mesenchymal stromal cells (MSCs) generating osteoblasts. In this review, we consider malfunctioning of MSCs as essential for osteoporosis. In osteoporosis, increased bone fragility and susceptibility to fractures result from increased osteoclastogenesis and insuffi cient osteoblastogenesis. MSCs are the common precursors for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
133
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(140 citation statements)
references
References 78 publications
6
133
0
1
Order By: Relevance
“…As a consequence, osteogenic differentiation from BMSCs is now recognized as an essential part integrated into bone remodelling. Accumulating evidences have also suggested that adipogenesis could play a significant role in bone metabolism (5,8,9,17,24,28,29). For example, since adipocytes and osteoblasts have the same ancestor, osteoblastogenesis and adipogenesis in the bone marrow are regulated in an opposite way, indicating that adipogenic conversion results in a reduction in osteoblast pool (24).…”
mentioning
confidence: 99%
“…As a consequence, osteogenic differentiation from BMSCs is now recognized as an essential part integrated into bone remodelling. Accumulating evidences have also suggested that adipogenesis could play a significant role in bone metabolism (5,8,9,17,24,28,29). For example, since adipocytes and osteoblasts have the same ancestor, osteoblastogenesis and adipogenesis in the bone marrow are regulated in an opposite way, indicating that adipogenic conversion results in a reduction in osteoblast pool (24).…”
mentioning
confidence: 99%
“…According to Gasser (2003), MSCs for the treatment of osteoporosis requires an osteogenic differentiation agent to be able to differentiate into osteoblasts. Pino et al (2012) reported that in patients with osteoporosis, MSCs tend to differentiate into adipose and not become osteoblasts because of interference on the intrinsic properties and the microenvironment of MSCs. Thus, MSCs therapy for osteoporosis patients brings new hope and melatonin can be considered as a supplement growth factors to obtain the maximum expansion of MSCs and can be used to manage the MSCs to be able to differentiate into osteogenic pathway (Gasser 2003;Zaminyet al 2008;Pino et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Second, underlying diseases in ASC donors were not considered in the present study. Several studies suggest that the number and functional activities of MSCs may be impaired in cells from patients with diseases such as diabetes and osteoporosis [27,51,52]. Third, the angiogenic potential of ASC-CM was evaluated only in the unstimulated condition.…”
Section: Discussionmentioning
confidence: 99%